Proceedings of the 2nd Public Health International Conference (PHICo 2017) 2018
DOI: 10.2991/phico-17.2018.21
|View full text |Cite
|
Sign up to set email alerts
|

A New Diabetic Management Using Standardized Diet and Post Meal Plyometric Exercise

Abstract: Prevalence of diabetes mellitus in the world has increased significantly in the last decades. Post meal physical exercise studies could improves blood glucose levels in diabetic patients. Plyometric exercise is a simple body movement that usually uses in body weight management. Therefore the aim of this study was to investigate the effect of combination of diet and post meal plyometric exercise on blood glucose levels of diabetic patients. A total of 19 diabetic patients were participated in this randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…We described new data from FBG and DPP4 of 0 and 60 minutes. However, due to the overlapping with the previous pilot study, the characteristic data of participants are partly in accordance with (and with permission to) the previous reports [ 17 , 18 ].…”
Section: Methodssupporting
confidence: 88%
See 4 more Smart Citations
“…We described new data from FBG and DPP4 of 0 and 60 minutes. However, due to the overlapping with the previous pilot study, the characteristic data of participants are partly in accordance with (and with permission to) the previous reports [ 17 , 18 ].…”
Section: Methodssupporting
confidence: 88%
“…is is a follow-up from two previous reports of the same preliminary study [17,18]. We have previously reported that after 7 days of treatment, consuming fruit first as the meal (FF) significantly reduced fasting DPP4 activity in patients with T2DM compared to the consumption of fruit as the last meal (FL) [17].…”
Section: Study Design Area and Periodmentioning
confidence: 90%
See 3 more Smart Citations